An examination of the rehabilitation process of adult male offenders with a mental disorder - Tyler, Suzannah Marie (2012)
This thesis includes an examination of the rehabilitation process of adult male offenders with a mental disorder. More specifically, it examines the effectiveness of treatment, and the community rehabilitation of adult mentally disordered offenders (MDOs). In Chapter 1 a literature review following a systematic approach examined the effectiveness of cognitive-behavioural interventions with adult MDOs in inpatient settings. Results revealed such interventions have the potential to improve: problem solving ability, social-cognitive skills, social adjustment, hostile and aggressive behaviour, and awareness of illness, ultimately bringing about a reduction of antisocial thinking and behaviour. The review findings were considered in relation to study quality and methodological limitations and recommendations for future research were discussed. In Chapter 2, an empirical research study gathered qualitative information of the experiences of adult male MDOs under Section 37/41 of the Mental Health Act (1983) who had been given a conditional discharge into the community. Results offered preliminary indications of influential factors at the individual level for the process of MDOs reintegration into the community. Recommendations for future research were discussed along with the clinical implications of the findings. A case study is presented in Chapter 3, evaluating the effectiveness of a cognitive-behavioural intervention with an adult male offender suffering anxiety and depression serving a sentence at HMP Cardiff. This case study demonstrated the importance of individual assessment and formulation in developing appropriate and effective interventions to meet client needs and highlighted the need to address prisoners’ mental health before they are released into the community. Future directions were considered with regards to working with offenders in prison settings. In Chapter 4 a critique of the CRIME-PICS-II (Frude, Honess & Maguire, 1994) offered a review of the tool in terms of its development, purpose, use, relevance to intervention planning and assessment, scientific and psychometric properties and its ease of use and accessibility. Further, it considered the tools applicability to forensic and clinical settings before exploring some of the limitations associated with its use. The implications of the thesis findings are finally considered in terms of existing limitations, clinical implications and future research.